Problemas de la tipicidad en la actio libera in causa en su estructura básica - Vásquez Cevallos, Fausto Ramiro (2024)
When it is exceptíonally stated that a wrong action is committed it must be imputed and for thls we must rely on the (alicactio libera in causa, Expression in Latín). This indicates an action taken by an individual in total use of his mental faculties and in a complete free and accountable condition, but that, for that particular moment the individual is incapable of guill. The modal suggests exception processing attribute or conduct engaged in default state. Toe exception modal undermines the principie of lraud or negligence, in thal fraud is a matter of fact. Criminal law and social status serve as a system of protection of socíety. Criminal law as a social state must be legitimized as an effective social protection system, whích ascribes the mission crime prevention measure, and only in the measure, what is necessary for that protectlon. The social status juslifies the intervention of the state to solve social problems, the (iuss ponendi, Expression in Latín), or !he legal right to punish. In my opinion this violates the principie of formal equafity and material. The principie of Legality is a fundamental princíple that all exercise of public authority should be subject to the will of law and jurisdiction. The structure of (omissio raleases in agendo, Expression in Latin ) is what causes more trouble to the criminality modal. This model, unlike !he exception, complains or crilicizes the conduct or outcome of the previous beh avior. This particular modal brings legal uncertainty, the option to punish the guarantor not clearly delined by law, creates uncertainty for legal processing. Eventualfy individuals unrelated to any criminal liabíllty have to suffer penalty aclions. Ali this is inappropriate for the rule of law.